The Influence of Competence and Work Facilities on Employee Performance with Work Motivation as an Intervening Variable at PT. Telekomunikasi Indonesia Jambi Branch - Mardoni, Mardoni; Yamali, Fakhrul Rozi; Hapsara, Osrita (Dinasti Publisher, 2025)
This study aims to determine and analyze the description of competency, work facilities, work motivation, and employee performance at PT. Telekomunikasi Indonesia Jambi Branch and to determine and analyze the influence of competency and work facilities on employee performance with work motivation as an intervening variable. The population in this study were all employees at PT. Telekomunikasi Indonesia Jambi Branch totaling 231 people consisting of 76 permanent employees and 155 contract employees. While the sampling technique in this study used purposive sampling. While for the analysis technique used in this study was through SmartPLS 3.0. Descriptively, competency, work facilities, motivation, and employee performance at PT. Telekomunikasi Indonesia Jambi Branch were perceived to have been going well. Meanwhile, from the hypothesis testing conducted, it can be concluded that competency and work facilities have a positive and significant influence on employee motivation and performance, both directly and through the mediating variable of motivation. These results confirm that increasing competency and work facilities will encourage motivation and have a significant impact on improving employee performance.